Characterisation of collagen scaffolds using x-ray microtomography - Smith, P; Sachlos, E; McDonald, S; Reis, N; Derby, B; Mummery, P; Czernuszka, J (2003)
Collagen scaffolds have been produced that incorporate predefined internal channels. The scaffolds were obtained with the aid of sacrificial moulds that have been manufactured using a rapid prototyping technique. A computer aided design file of the mould was created and then realised using an ink-jet printer. A dispersion of collagen was then cast into the mould and frozen. Ethanol was used to dissolve the mould leaving the collagen, which was then freeze dried to produce the final product. The scaffold was then analysed using X-ray microtomography (XMT) to determine whether the desired internal structure was obtained. It was found necessary to add saturated potassium iodide (KI) solution to the scaffold in order to analyse it satisfactorily by XMT. The resultant images indicate that the desired internal structure was obtained.